Investigation of slopes on the Takanoobane lava dome using the resistivity imaging method - Y. Kochi; T. Kariya; D. Matsumoto; T. Hirose; H. Hazarika (Lowland Technology International, 2018)
In the Kumamoto earthquake in 2016, landslides occurred in many place on moderately inclined slope in the Takanoobane lava dome. In this research, we focus on the orange-colored pumice layer (Kpfa), which is predisposed to the landslide, and show the distribution using the resistivity imaging method on a slope where no landslide has occurred. According to the survey results, the slope without the landslide was observed when the slope was hard to slip mechanically due to the Kpfa layer was distributed in a shallow place or paleogeography of the foundation layer surface (Takanoobane lava)